2008
DOI: 10.1001/archfaci.10.5.335
|View full text |Cite
|
Sign up to set email alerts
|

Soft-Tissue Augmentation With Calcium Hydroxylapatite

Abstract: To evaluate histologically the extent and character of tissue in-growth after injection of calcium hydroxylapatite for soft-tissue augmentation. Methods: Prospective case series of 8 patients from a private facial plastic surgery practice. Each patient was injected subdermally between the dermis and the subcutaneous fat with 0.1 mL of calcium hydroxylapatite in the superior postauricular sulcus. One month later, 2 patients underwent excision of the injected material, which was submitted for routine histologica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
3

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 9 publications
(11 reference statements)
1
14
3
Order By: Relevance
“…In this way, a slow dispersion of the microgranular content in the close extracellular matrix environment, freely into the ground substance and/or between the collagen fibres, would permit a more homogeneous distribution of microgranules. These observations do not agree with some previous research works, reporting lymphocytic infiltrate associated with giant cells engulfing spherules, without migration of the implanted material, and supporting a phagocytotic mechanism [15, 16]. …”
Section: Discussioncontrasting
confidence: 94%
See 1 more Smart Citation
“…In this way, a slow dispersion of the microgranular content in the close extracellular matrix environment, freely into the ground substance and/or between the collagen fibres, would permit a more homogeneous distribution of microgranules. These observations do not agree with some previous research works, reporting lymphocytic infiltrate associated with giant cells engulfing spherules, without migration of the implanted material, and supporting a phagocytotic mechanism [15, 16]. …”
Section: Discussioncontrasting
confidence: 94%
“…While some authors were supporting a stimulatory induction to form new collagen as the gel carrier is metabolized [3, 15], others did not give evidence of new collagen deposition, “may be due to the small size of examined samples”, as stated by the authors here cited [16]. …”
Section: Discussionmentioning
confidence: 96%
“…The temporary increase in collagens I and III does however not explain the long‐term improvement obtained by CaHA as mature collagen incorporated into extracellular matrix has a half‐life of >200 years in bone, cartilage, and tendons and of about 15 years in skin (Heinemeier, Schjerling, Heinemeier, Magnusson, & Kjaer, ; Libby, Berger, Mead, Alexander, & Ross, ; Verzijl et al, ). Indeed, the study of Holzapfel, Mangat, and Barron () could not find any evidence of mature collagen formation by CaHA (Holzapfel et al, ). Another investigation using light and electron microsopies described a well‐represented Golgi apparatus in fibroblasts in vicinity to CaHA (Zerbinati, D'Este, Parodi, & Calligaro, ).…”
Section: Calcium Hydroxyl Apatite Out Of the Facementioning
confidence: 96%
“…As outlined previously, if nodules do occur, they can be treated in part with intralesional injection and/or surgical excision. Theoretical concerns of bone stimulation following CaHA injection have been raised, but to date no studies have shown this theory to be true ( 167 ). Nonetheless, it is still recommended that this fi ller not come in direct contact with bone when injecting into the preperiosteal plane ( 5 ).…”
Section: Calcium Hydroxylapatitementioning
confidence: 99%